Kepemimpinan transformasional dalam pembentukan Organizational Citizenship Behavior (OCB) Polisi: Kepuasan kerja sebagai mediator: Transformational leadership in the formation of Police Organizational Citizenship Behavior (OCB): Job satisfaction as a mediator - Fatuhrahmah, Ufi; Ardian, Muhammad Eka Deny; Husada, Muhammad Rizky (Persona:Jurnal Psikologi Indonesia, 2023)
Previous research emphasizes the importance of Organizational Citizenship Behavior (OCB) in public institutions, including the police. However, there is limited literature that examines how OCB subtypes are formed. Considering the centrality of the leader figure in the police, this research investigates the role of transformational leadership in the formation of OCB through attitudinal mechanisms, namely job satisfaction. The quantitative research involved 251 participants, chosen via cluster sampling from a single Resort/Departmental Police Force in Indonesia. This participant willingly completed three main scales: the OCB scale, the job satisfaction scale, and the transformational leadership scale. Data processing used mediation analysis with JASP software JASP 0.17.3 (Intel). The results align with previous findings, which stated a significant positive relationship between transformational leadership and OCB, which was mediated by job satisfaction. Furthermore, this research shows that only the OCB-Individual (OCBI) subtype (courtesy and altruism) is related to transformational leadership through the mediation of job satisfaction. Discussions and implications are outlined in detail, both for police institutions and future researchers